Incorporating Out-Patient Data From CD-R Into the Local PACS Using DICOM Worklist Features - van Ooijen, P. M. A. (Springer-Verlag, 2005)
With the introduction of digital imaging in radiology, CD-Rs are increasingly used to distribute patient materials. This study investigates the application of a new software package and work protocol to integrate out-hospital data into the local PACS (picture archive and communication system) archive, which is hampered by differences in patient numbers. A one-month trial was started to import CD-Rs from two departments (radiotherapy and radiology). Seventy CD-Rs were collected from 20 different hospitals holding data of eight different modality types and published by eight different software packages from different vendors. All CD-Rs were successfully transferred into the PACS. The new software and work protocol provide an easy way of introducing the out-hospital data into the PACS. CD-Rs can be destroyed after transfer to PACS, eliminating physical storage. Furthermore, all data can now be viewed and reported using the default viewers of the hospital and no additional training of staff is required.